Expression of HSP70 in the brain of rats during experimental cerebral ischemia modeling and on the background of neuroprotection - Belenichev, I. F.; Pavlov, S. V.; Bukhtiayarova, N. V.; Samura, I. B.; Egorov, A. N.; Semenov, D. M.; Бєленічев, Ігор Федорович; Павлов, Сергій Васильович; Бухтіярова, Ніна Вікторівна; Самура, Ірина Борисівна; Єгоров, Олександр Миколайович; Семенов, Денис Михайлович (Bulgaria: Hikari Ltd, 2017)
Experimental research has found that acute cerebral ischemia modeling in rats is accompanied by a significant increase in the main marker of oxidative degradation of proteins – nitrotyrosine beginning from the first day of the experiment. Concurrently there has been a decline in stress-protein HSP70 in brain tissue. Administration of Cerebrocurin for 4 days has led to a decrease in the levels of nitrotyrosine, as well as to increase in the expression of stress-responsive protein HSP70 in the acute period of cerebral ischemia.
Keywords: HSP70; cerebral ischemia; neuroprotection